2013
DOI: 10.1097/ss.0b013e31829a2826
|View full text |Cite
|
Sign up to set email alerts
|

DOC and DON Release and Reactive Soil Pools in Urban and Remnant Soils

Abstract: Release of dissolved organic carbon (DOC) and nitrogen (DON) from subtropical urban soils has had little investigation, even though the growth of metropolitan areas is unprecedented in southern states. The time of initial disturbance from native or agricultural to urban land use and irrigation with sodic water may compromise urban soils' ability to retain DOC and DON. We examined 21 soils from beneath remnant native land use and urban land use in south-central Texas. Soils were collected from five classes of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…As stated previously, increased soil sodicity increases aggregate dispersion and additional substrate is likely provided through desorption of DOM. This increase in carbon or DOC was recognized with exposure to highly sodic water (Wong et al, 2008;Aitkenhead-Peterson and Cioce, 2013) which was the case at our irrigated urban sites. In fact, the two sites with the lowest %BDOC in this study had the highest DOC release and reactive soil pools (Aitkenhead-Peterson and Cioce, 2013).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…As stated previously, increased soil sodicity increases aggregate dispersion and additional substrate is likely provided through desorption of DOM. This increase in carbon or DOC was recognized with exposure to highly sodic water (Wong et al, 2008;Aitkenhead-Peterson and Cioce, 2013) which was the case at our irrigated urban sites. In fact, the two sites with the lowest %BDOC in this study had the highest DOC release and reactive soil pools (Aitkenhead-Peterson and Cioce, 2013).…”
Section: Resultsmentioning
confidence: 80%
“…Given the global increase in urbanization, it was important to examine how urban soils might differ from remnant soils in terms of C cycling. More recent work in the study area showed that increased release of DOC from soil exchange sites and higher DOC reactive soil pools could be explained by time since initial soil disturbance (when the house was built), soil pH, and soil cations (Aitkenhead-Peterson and Cioce, 2013). Soil cations, specifically sodium, increased in urban soils as a result of high sodium in irrigation water (Aitkenhead-Peterson and Cioce, 2013).…”
Section: Introductionmentioning
confidence: 96%